LEGISLATIVE ADJUSTING OF INFORMATIVE ACCOMPANIMENT OF ELECTIONS IN UKRAINE - Рум’янцева, С.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
On the basis of the analysis of current legislation of Ukraine about elections, and also actual tendencies in the development of mass media communication, attention is paid to methods, possibility and necessity of adjusting of informative accompaniment of electoral process in Ukraine. Attention is also paid to the absence of the legal adjusting of current electronic networks.